Intersectional identities of Nyai and their resistance to oppressiveness in Indonesian short stories - Mukti, Wijang Iswara; Budiyanto, Dwi; Hartono, Hartono; Suroso, Suroso (Diksi, 2023)
The dominant values of colonialism influenced indigenous society in defining the status of women and worsening their treatment. This influence can be seen in the concubinage system experienced by the nyai. The figure of nyai not only received systemic oppression, but was also portrayed badly through colonial-era literature. In contrast to colonial-era literature, Indonesian literature in the postcolonial era tries to represent the figure of nyai with her intersectional identity, as well as reveal their resistance to the patterns of systemic oppression experienced in the concubinage system. This research uses a descriptive-qualitative research design. This research design aims to describe the intersectional identity of nyai and their resistance to forms of oppressiveness in Indonesian short stories. The data and information found from the selected short stories will be interpreted qualitatively using Kimberle Crenshaw's intersectionality perspective. The data sources are selected porpusively, namely Indonesian short stories that represent nyai and concubinage in the Dutch East Indies, including (1) Stambul dua Pedang (2013), (2) Racun untuk Tuan (2011), and (3) Keringat dan Susu (2010), all three by Iksaka Banu, and (4) Kutukan Dapur (2003) by Eka Kurniawan. The data are in the form of story facts that include story sequences, characters, settings, themes, and other literary means from data sources that contain information related to the research problem. The data was obtained using reading and note-taking techniques. Furthermore, it was analyzed qualitatively by using Crenshaw's intersectionality perspective. The results of this study show that the intersectionality identity of the nyai in the four short stories above is a woman with charming physique and skills, colonized indigenous race, poverty and low social class, patriarchal system, and colonial system. The oppressions found are intimidation, expulsion, denial of rights as a woman, and murder. The resistance found is utilizing one's own skills, help from other parties, enjoying the role and surrendering to the situation.Keywords: Intersectional identity, resistance, oppression, subaltern, Crenshaw